Effects of Graded Levels of Raw Baobab (Adansonia Digitata) Seed Meal on the Performance of Broiler Chicken (British Journal of Multidisciplinary and Advanced Studies, 2025)
This study effect of graded levels of raw Baobab (Adansonia digitata) seed meal on the performance of broiler chickens. 200-day-old broiler chicks were randomly assigned to five treatment groups, each consisting of 40 chicks, with four replicates (10 chicks per replicate) in a completely randomized design. The dietary treatments included different inclusion levels of raw baobab seed meal (RBSM) at 0%, 10%, 20%, 30%, and 40%. The proximate analysis of the raw baobab seed meal revealed a crude protein content of 32.25% and a crude fibre content of 7.10%. The results showed that the final body weight of chickens on the control diet was significantly higher (1344.40 g, p < 0.05) compared to those fed the treatment diets (RBSM). The chickens consuming RBSM had a poorer feed conversion ratio of ranged from 3.50 – 4.54. Moreover, key carcass characteristics, internal organ weights, and haematological indices were also significantly affected (p < 0.05).